Vietnamese teachers’ attitudes toward online professional development programs - Dao Thi Hong Van; Ha Hoang Quoc Thi; Nguyen Duy Khang (Journal of Educational Management and Instruction (JEMIN), 2022)
In addition to the massive deployment of online learning among students worldwide, virtual training has also become a necessity to ensure the demand of teacher professional development. Exploring teachers’ attitudes toward online training programs helps educational stakeholders in understanding their expectations toward professional training modes, which positively contribute to boosting the effectiveness of career development programs. The present study sheds some light on Vietnamese English teachers’ attitudes toward online professional development programs. Twenty-five EFL teachers in Can Tho city Vietname took part in the research by providing answers to the questionnaire delivered using Google Form application; ten of them volunteered to attend further interview sections. The results of pair sample t-tests show that the English teachers preferred face-to-face to online training programs. In addition, the qualitative findings further revealed that they had no offense to online training mode, yet deny its sole implementation for all future professional development activities. Especially, most teachers approved the practice of online training in the context of the COVID-19 pandemic. Moreover, some of them started to acknowledge a blended teacher training program as they are relying in its affordances and accessibility. Considering the crucial role of development programs for teachers, the findings of this study contribute to providing input enhancement for teacher professional training stakeholders in Vietnam.